2023
DOI: 10.3390/healthcare11020160
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Labor Force Participation on Elderly Health in China

Abstract: In the context of the deepening of population aging and the trial implementation of a progressive retirement delay policy in China, understanding the relationship between the labor force participation and health status of the elderly will not only enrich relevant research but also help the elderly better achieve their goals of active aging and aging. Using the 2018 China Health and Retirement Longitudinal Study, this paper first established multiple linear regression models to analyze the impact of labor force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previous research concluded different findings, where some studies found a significant protective effect of labor participation in later life against declining functional limitations in men, but less or not at all in women, 18,21 and other studies found that the negative effects of re-employment after retirement on mental health were greater in women than in men or there was no effect on men. 20,21 Plausible explanations for the reported sex differences might be related to the differences in gendered socialization and gender variations in social roles or family responsibilities. 20,55,56 The present study has important implications for social policy evaluation and public health practice.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous research concluded different findings, where some studies found a significant protective effect of labor participation in later life against declining functional limitations in men, but less or not at all in women, 18,21 and other studies found that the negative effects of re-employment after retirement on mental health were greater in women than in men or there was no effect on men. 20,21 Plausible explanations for the reported sex differences might be related to the differences in gendered socialization and gender variations in social roles or family responsibilities. 20,55,56 The present study has important implications for social policy evaluation and public health practice.…”
Section: Discussionmentioning
confidence: 95%
“…With regard to sex subgroups, the present results showed significant impact of post‐retirement work on HRQOL among men, and only marginal significant impact among women, suggesting no sex specificity. Previous research concluded different findings, where some studies found a significant protective effect of labor participation in later life against declining functional limitations in men, but less or not at all in women, 18,21 and other studies found that the negative effects of re‐employment after retirement on mental health were greater in women than in men or there was no effect on men 20,21 . Plausible explanations for the reported sex differences might be related to the differences in gendered socialization and gender variations in social roles or family responsibilities 20,55,56 …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations